Factors associated with practice of smoking cessation guidelines among primary care doctors in northern Malaysia: a cross sectional study - Abdul Rashid, Aneesa; Hashim, Norazila; Govadan, Premmla Devi; Surennaraina, Punitha; Zainuddin, Zarina Zakiah; Nadarajan, Yoggeswary; Poey, Ling Soo (Springer Nature, 2025)
Introduction: Smoking prevalence is high in Malaysia, particularly in the state of Kedah, according to the National Health Morbidity Survey 2019. Strengthening primary care smoking cessation services is crucial. This study aimed to identify factors associated with adherence to the Malaysian Clinical Practice Guideline on the Treatment of Tobacco Use Disorder among government primary care doctors in Kedah. Methods: A cross-sectional survey was conducted among 163 public primary care doctors in the Kulim and Kuala Muda districts of Kedah. Knowledge, attitude, and practice related to smoking cessation guidelines were assessed using a validated questionnaire. Scores were categorized as good or poor. Good knowledge and practice required full marks, while good attitude was defined as scoring five or more out of ten. Associations between knowledge, attitude, sociodemographic, and practice were analysed. Results: The majority of respondents were female (67.5%), Malay (65%), with a mean age of 35.4 ± 5.23 years. Most demonstrated good attitude (69.9%) but had poor knowledge (80.4%) and practice (86.5%) scores. Poor knowledge was significantly associated with poor practice (AOR = 3.331, p = 0.017). Conclusion: Primary care doctors in the Kedah state demonstrated a positive attitude toward smoking cessation but exhibited gaps in knowledge and practice, with lower knowledge scores linked to poor practice. Targeted interventions, including guideline-focused training for non-specialists, new medical officers, and those without prior training, are recommended to enhance smoking cessation management.